A System Bioinformatics Approach Predicts the Molecular Mechanism Underlying the Course of Action of Radix Salviae Reverses GBM Effects. (16th December 2021) - Jiaojiao, Sun; Yuping, He; Yajuan, Li; Guangyi, Liu; Qiuhong, Li; Shengbiao, Li; Hong, Yu
Abstract : Objective . This study used in vitro techniques to investigate the therapeutic effect of Radix Salviae on human glioblastoma and decode its underlying molecular mechanism. Methods . The active components and targets of the Radix Salviae were identified from the Traditional Chinese Medicine Systems Pharmacology Database (TCMSP). The targets of human glioblastoma were obtained from the GeneCards Database. The Radix Salviae-mediated antiglioblastoma was evaluated by Gene Ontology (GO) analyses and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses. Finally, mechanism of action of Radix Salviae against human glioblastoma was deduced by molecular docking and experiments. Results . We screened 66 active ingredients and 45 targets of the Radix Salviae. The enrichment analysis based on the targets mentioned above suggested a possible role in protein phosphorylation, cell transcription, apoptosis, and inflammatory factor signaling pathways. Further study demonstrated that cryptotanshinone, an essential component of Radix Salviae, played a significant role in killing human glioblastoma cells and protecting the body by inhibiting the AKT, IKB, and STAT3 signaling pathways. Conclusions . Radix Salviae could inhibit the proliferation and invasion of human glioblastoma by regulating STAT3, Akt, and IKB signaling pathways. Radix Salviae has potential therapeutic value in the future for human glioblastoma.